2018
DOI: 10.1037/xhp0000492
|View full text |Cite
|
Sign up to set email alerts
|

Volitional and automatic control of the hand when reaching to grasp objects.

Abstract: When picking up an object, we tend to grasp at contact points that allow a stable grip. Recent studies have demonstrated that appropriate grasp points can be selected during an ongoing movement in response to unexpected perturbations of the target object. In this study, we tested whether such online grip adjustments are automatic responses or can be controlled volitionally. Subjects performed virtual grasping movements toward target 2D shapes that sometimes changed shape or orientation during movement. Unlike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…Participants. To determine the number of participants to typically observe language-switch costs with a comprehension task, we decided to look into prior research that found significant language-switch costs (for a similar technique, see, e.g., Chen & Saunders, 2018;Questienne, van Dijck, & Gevers, 2018;Won & Geng, 2018). 1 When we started this study, published comprehension-based language switching studies had tested between 16 (Thomas & Allport, 2000) and 26 participants (Hirsch et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Participants. To determine the number of participants to typically observe language-switch costs with a comprehension task, we decided to look into prior research that found significant language-switch costs (for a similar technique, see, e.g., Chen & Saunders, 2018;Questienne, van Dijck, & Gevers, 2018;Won & Geng, 2018). 1 When we started this study, published comprehension-based language switching studies had tested between 16 (Thomas & Allport, 2000) and 26 participants (Hirsch et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…For example, when picking up an object, one tends to grasp at contact points that allow a stable grip. Appropriate grasp points can be re-selected during an ongoing movement in response to unexpected perturbations of the target object, suggesting that automatic control mechanisms guide the fingers to appropriate grasp points distinctly from those involved with volitional control [89]. Volitional control with meta-level consciousness is only required when a new purpose for a new project is formulated.…”
Section: Behavior Control Systemmentioning
confidence: 99%
“…Participants performed a reaching stop-signal task (e.g. Chen & Saunders, 2018) which included the presentation of odour primes. Each trial started with a black screen for 500 ms during which clean air was delivered.…”
Section: Methodsmentioning
confidence: 99%